Presenting and explaining a model for developing human resources policies in education - Borzoei, Mohammad (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: Human resource policies create and sustain a suitable infrastructure for developing new products, technologies, and organizational procedures by promoting employees' values of creativity, cooperation, independence, and ambition. Therefore, the research aimed to present and explain a model for developing human resources policies in education.Method: The present study was qualitative. The process of conducting research in the way of processing the data theory of the foundation includes research questions, note-taking and data collection, analysis, theoretical sampling, and theoretical saturation, writing and compiling theory, and comparing texts. The analysis process started with open coding and ideally ended with selective coding. In order to collect the primary components, 50 domestic and foreign articles and book titles were studied using the criterion-based purposeful sampling method. With this number of samples, the researcher reached theoretical saturation. After coding and categorizing the components (by 20 experts) using the Kendall coefficient, the reliability of the components was estimated at 88%.Results: The results showed that the dimensions and components can be classified into 5 main dimensions and 50. According to the main loads, the research model has good validity.Conclusion: The results of the present study showed that this planning model can be considered as a continuous and dynamic process to improve employees and achieve organizational goals.